(untitled) (RuMoRes, 2010)
This paper presents considerations about lexical choices used as meaning construction strategies in journalistic texts. Such choices are seen as cultural markers or filters used by the journalist to represent a fact to the reader who shares the target culture with him, but who does not know about the socio-cultural context where the fact takes place. Thus, the journalist is seen as a translator of facts, while the concept of translation shifts from the source text to news fact itself (ZIPSER, 2002). Based on the German functionalism (NORD, 1991) and on journalism as a socio-cultural map (ESSER, 1998), this paper demonstrates the interface translation-journalism through these concepts and also through some news reports about the “September 11th”, as a parallel corpus, published in Veja and TIME magazines.